Green ICT and Environmental Sustainability: Awareness of Malaysian Teachers - Adawiah Ahmad Rashid, Rabiatul; Sukri Shafie, Mohd (International Journal of Engineering and Technology, 2018)
Green ICT that has been outlined by the Ministry of Energy, Green Technology and Water (KeTTHA) is seen to be important to balance the implementation of ICT in schools where elements of environmental preservation from inefficiency use of technology can be applied from teachers to students at the early stage. This study examined teachersâ€™ awareness of Green ICT and environmental sustainability in the aspect of teachersâ€™ knowledge, attitude and practices as proposed by the KAP Model.Â The sample comprised of 358 secondary school teachers. Descriptive statistics, independent sample T-Test, One-Way ANOVA and multiple regression were used to analyze the data. Result revealed that a most of the teacher lack of knowledge on Green ICT, but teachersâ€™ attitudes and teachersâ€™ practices found to be high. The important of knowledge gaps related to, and factors influencing the sustainability of attitudes and practices on Green ICT were identified and discussed. Â